Caracterização e avaliação da atividade antimicrobiana de membrana de gelatina contendo timol complexado em β-ciclodextrina - Santos, Lana Naiadhy Silva (2019)
Thymol, a phenolic compound of the monoterpene class found in several vegetal species, have been widely used in conventional pharmaceuticals formulations due to the broad pharmacologic activity, particularly the antimicrobial one.Such compound presents high volatility, limited water solubility and low bioavailability, what hinders its therapeutic application. Studies conducted using thymol with β-cyclodextrin (β-CD) have been shown as promising in the enhancement of the physical-chemical and pharmacological characteristics of this compound. The combination of mucoadhesive systems with inclusion complexes (IC) is an interesting strategy from the pharmacokinetic point of view for the treatment of lesions of the oral cavity. These systems promote longer-lasting contact of the drug with the mucosa, thus significantly improving the therapeutic performance of many substances. Henceforth, the aim of this study was to develop, characterize and evaluation of antimicrobial activity of the gelatin mucoadhesive membrane containing tymol complexed in β-cyclodextrin. The membranes were obtained by means of the solvent evaporation technique and the IC by means of lyophilization in molar ratios of 1:1. The characterization of the membranes was performed through the techiniques of differential scanning calorimetry (DSC), thermogravimetry/derivative thermogravimetry (TG/DTG), X-ray diffraction (DRX), Fourier transform infrared attenuated total reflectance spectroscopy (FT-IR/ATR), scanning electron microscopy (MEV), swelling capacity and mucoadhesion. The entrapment efficiency (EE) was performed with highperformance liquid chromatography (HPLC) and the cellular viability assay with the resazurin reduction method in J774-G8 macrophages. The assessment of the microbiological activity was performed by disk diffusion method with Escherichia coli and Staphylococcus aureus. The results showed that the addition of the IC in the membranes enabled alterations in the rates of intumescence (>60%) parameters favorable to mucoadhesion. Moreover, they presented antimicrobial activity revealing inhibition of the growth of the bacterial strains tested. Therefore, it is conclude from the result, that mucoadhesive systems containing tymol inclusion complexes may be promising in the treatment of oral infectious lesions.